NEUROMUSCULAR INJURY METHOD IN DIFFERENT STRENGTH SPORTS DAMAGE - Yang,Yongfen (2021)
ABSTRACT Introduction: Sports muscle injury is a common phenomenon in sports, and most of it is caused by intense exercise done for a long time. Objective: The effect of high intensity mode (HI) speed endurance training on the muscle injury of athletes. Methods: 14 sprinters were recruited; the muscle injury indexes of the subjects were tested 15 min before and 24 h, 48 h and 72 h after speed endurance training in HV mode and HI mode (high volume mode and high intensity mode, respectively). Results: The results of this study showed that both high amount and HI mode speed endurance training caused a certain degree of injury to the subjects’ muscles, but the injury caused by HI mode speed endurance training to the muscles was more serious than that caused by high amount (P < 0.05). Conclusions: HI mode speed endurance training causes a certain degree of injury to the subjects’ muscle, but it causes more serious injury than high volume mode speed endurance training. Level of evidence II; Therapeutic studies - investigation of treatment results.